Discovery and characterization of ORM‐11372, a novel inhibitor of the sodium‐calcium exchanger with positive inotropic activity. (10th November 2020) - Otsomaa, Leena; Levijoki, Jouko; Wohlfahrt, Gerd; Chapman, Hugh; Koivisto, Ari‐Pekka; Syrjänen, Kaisa; Koskelainen, Tuula; Peltokorpi, Saara‐Elisa; Finckenberg, Piet; Heikkilä, Aira; Abi‐Gerges, Najah; Ghetti, Andre; et al.
Abstract : Background and Purpose: The lack of selective sodium–calcium exchanger (NCX) inhibitors has hampered the exploration of physiological and pathophysiological roles of cardiac NCX 1.1. We aimed to discover more potent and selective drug like NCX 1.1 inhibitor. Experimental Approach: A flavan series‐based pharmacophore model was constructed. Virtual screening helped us identify a novel scaffold for NCX inhibition. A distinctively different NCX 1.1 inhibitor, ORM‐11372, was discovered after lead optimization. Its potency against human and rat NCX 1.1 and selectivity against other ion channels was assessed. The cardiovascular effects of ORM‐11372 were studied in normal and infarcted rats and rabbits. Human cardiac safety was studied ex vivo using human ventricular trabeculae. Key Results: ORM‐11372 inhibited human NCX 1.1 reverse and forward currents; IC50 values were 5 and 6 nM respectively. ORM‐11372 inhibited human cardiac sodium 1.5 ( I Na ) and hERG KV 11.1 currents ( I hERG ) in a concentration‐dependent manner; IC50 values were 23.2 and 10.0 μM. ORM‐11372 caused no changes in action potential duration; short‐term variability and triangulation were observed for concentrations of up to 10 μM. ORM‐11372 induced positive inotropic effects of 18 ± 6% and 35 ± 8% in anaesthetized rats with myocardial infarctions and in healthy rabbits respectively; no other haemodynamic effects were observed, except improved relaxation at the lowest dose. Conclusion and Implications: ORM‐11372, a unique, novel, and potent inhibitor of human and rat NCX 1.1, is a positive inotropic compound. NCX inhibition can induce clinically relevant improvements in left ventricular contractions without affecting relaxation, heart rate, or BP, without pro‐arrhythmic risk.